Global REACH 2018: the adaptive phenotype to life with chronic mountain sickness and polycythaemia. (8th August 2021) - Hansen, Alexander B.; Moralez, Gilbert; Amin, Sachin B.; Simspon, Lydia L.; Hofstaetter, Florian; Anholm, James D; Gasho, Christopher; Stembridge, Mike; Dawkins, Tony G.; Tymko, Michael M.; Ainslie, Philip N.; Villafuerte, Francisco; et al.
Abstract : Key points: Humans suffering from polycythaemia undergo multiple circulatory adaptations including changes in blood rheology and structural and functional vascular adaptations to maintain normal blood pressure and vascular shear stresses, despite high blood viscosity. During exercise, several circulatory adaptations are observed, especially involving adrenergic and non‐adrenergic mechanisms within non‐active and active skeletal muscle to maintain exercise capacity, which is not observed in animal models. Despite profound circulatory stress, i.e. polycythaemia, several adaptations can occur to maintain exercise capacity, therefore making early identification of the disease difficult without overt symptomology. Pharmacological treatment of the background heightened sympathetic activity may impair the adaptive sympathetic response needed to match local oxygen delivery to active skeletal muscle oxygen demand and therefore inadvertently impair exercise capacity. Abstract: Excessive haematocrit and blood viscosity can increase blood pressure, cardiac work and reduce aerobic capacity. However, past clinical investigations have demonstrated that certain human high‐altitude populations suffering from excessive erythrocytosis, Andeans with chronic mountain sickness, appear to have phenotypically adapted to life with polycythaemia, as their exercise capacity is comparable to healthy Andeans and even with sea‐level inhabitants residing at high altitude. By studying this unique population, which has adapted through natural selection, this study aimed to describe how humans can adapt to life with polycythaemia. Experimental studies included Andeans with ( n = 19) and without ( n = 17) chronic mountain sickness, documenting exercise capacity and characterizing the transport of oxygen through blood rheology, including haemoglobin mass, blood and plasma volume and blood viscosity, cardiac output, blood pressure and changes in total and local vascular resistances through pharmacological dissection of α‐adrenergic signalling pathways within non‐active and active skeletal muscle. At rest, Andeans with chronic mountain sickness had a substantial plasma volume contraction, which alongside a higher red blood cell volume, caused an increase in blood viscosity yet similar total blood volume. Moreover, both morphological and functional alterations in the periphery normalized vascular shear stress and blood pressure despite high sympathetic nerve activity. During exercise, blood pressure, cardiac work and global oxygen delivery increased similar to healthy Andeans but were sustained by modifications in both non‐active and active skeletal muscle vascular function. These findings highlight widespread physiological adaptations that can occur in response to polycythaemia, which allow the maintenance of exercise capacity. Key points: Humans suffering from polycythaemia undergo multiple circulatory adaptations including changes in blood rheology and structural and functional vascular adaptations to maintain normal blood pressure and vascular shear stresses, despite high blood viscosity. During exercise, several circulatory adaptations are observed, especially involving adrenergic and non‐adrenergic mechanisms within non‐active and active skeletal muscle to maintain exercise capacity, which is not observed in animal models. Despite profound circulatory stress, i.e. polycythaemia, several adaptations can occur to maintain exercise capacity, therefore making early identification of the disease difficult without overt symptomology. Pharmacological treatment of the background heightened sympathetic activity may impair the adaptive sympathetic response needed to match local oxygen delivery to active skeletal muscle oxygen demand and therefore inadvertently impair exercise capacity.